Hydropolitics and issue-linkage along the Orontes River Basin: an analysis of the Lebanon-Syria and Syria-Turkey hydropolitical relations - Conker, Ahmet; Hussein, Hussam (SPRINGER, 2020)
The Orontes River Basin is among the least researched transboundary water basins in the Middle East. The few studies on the Orontes have two main theoretical and empirical shortcomings. First, there is a lack of critical hydropolitics studies on this river. Second, those studies focus on either the Turkish-Syrian or Lebanese-Syria relations rather than analysing the case in a holistic way. Gathering both primary (international agreements, government documents, political statements and media outlets) and secondary sources, this paper seeks to answer how could Syria, as the basin hydro-hegemon, impose its control on the basin? This study argues that the lack of trilateral initiatives, which is also reflected in academic studies, is primarily due to asymmetrical power dynamics. Accordingly, Syria played a dual-game by excluding each riparian, Turkey and Lebanon, and it dealt with the issue at the bilateral interaction. Syria has used its political influence to maintain water control vis-a-vis Lebanon, while it has used non-cooperation with Turkey to exclude Turkey from decision-making processes. The paper also argues that the historical background and the political context have strongly informed Syria's water policy. Finally, given the recent regional political developments, the paper finds that Syria's power grip on the Orontes Basin slowly fades away because of the changes in the broader political context.
Keywords: Orontes River; Hydropolitics; Transboundary water; Issue-linkage; Broader political context; HYDRAULIC DEVELOPMENT; WATER; POWER; COOPERATION; HEGEMONY; POLITICS; ROGUN; DAM; Business & Economics; Environmental Sciences & Ecology; Government & Law